Detection of Explosive Vapors: The Roles of Exciton and Molecular Diffusion in Real‐Time Sensing. Issue 21 (26th October 2016) - Ali, Mohammad A.; Shoaee, Safa; Fan, Shengqiang; Burn, Paul L.; Gentle, Ian R.; Meredith, Paul; Shaw, Paul E.
Abstract: The front cover artwork is provided by the Centre for Organic Photonics & Electronics at the University of Queensland (Australia). The image shows how the real‐time response of a luminescent sensing film to explosive analyte vapors is governed by the propagation of a high‐concentration analyte front through the film rather than long‐range exciton diffusion. Read the full text of the article at10.1002/cphc.201600767 . Abstract : "By correlating the uptake of nitroaromatic (explosive) vapor by a porous conjugated polymer film with the quenching of the fluorescence the origins of the high sensitivity of this material are probed..…" This and more about the story behind the front cover can be found in the Communication at10.1002/cphc.201600767 .